Phenotypic stability of soybean cultivars in southeastern Rio Grande do Sul, Brazil - Vernetti, Francisco de Jesus; Gastal, Mário Franklin da Cunha; Zonta, Élio Paulo (Pesquisa Agropecuaria Brasileira, 2014)
The phenotypic stability of 13 cultivars of soybean Glycine max (L.) Merrill, in 35 environments of three counties of southeastern Rio Grande do Sul, Brazil, was evaluated by a segmented regression analysis: E(Y) = B 0 + B,X ± 132X 1 . The cultivars recommended for planting in that state were six early (V-VI), theree medium (VII), two semi-late (VIII) and two late (VIII). All responded similarly to the favorable environments. Their B2 regression coefficients were non-significant. The Hampton cultivar had the highest yield and the best stability, with nonsignificant 13, regression coefficient. Consecutive years corresponded to diverse environment, in the counties where the experiments were carried out. The best environments were related to the best soil conditions and the worse ones, most times were related to the poorly-drained Planosol and to the red-yellow podzolic soil which was chemically poor. In both the water deficit was more frequent and more intenso. As none B2 coefficient was significant, it would be possible to adjust only one regression equation, independently of positive and negative environments (Eberhart & Russeil method).